Peningkatan Genetik Domba Merino Melalui Teknologi IB Mengunakan Pejantan Merino dan Pengolahan Pakan di Kecamatan Junrejo Malang - Anom Adnyana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2018)
The objective of this study was to disseminate the technology of Artificial Insemiation (AI) and Food Processing. This activity expected to help the Merino sheep partner group for overcoming their problems which subsequently it can improve their income. The methods used in this study was to give insight knowledge and simple technology to the selected merino sheep partner group. Based on the discussion with merino sheep partner group, several activities were carried out, i.e.: (1) facilitating some good quality of merino sheep lifestoocks, (2) providing technology of alternative food production with cooper, (3) training of production and financial management, (4) demo-reproduction management and (5) monitoring and evaluation. The result of this study showed that the merino sheep partner group could master the technique of the technique of selecting superior sires ,parent management, fertilizer production engineering, manufacture and management of alternative feed production and reproduction as well as the financial well.